POLYCLINIC MEDICAL RECORDS APPLICATIONS IN PUBLIC OFFICE METEOROLOGY AND GEOPHYSICS AGENCY USING MICROSOFT VISUAL BASIC 6.0 - Mai munawaroh; Irfan.SKom.MMSI Irfan.SKom.MMSI (Jurnal Sistem Informasi, 2005)
In the world of health, health is a very important thing that is more valuable thananything else that was awarded by Almighty God to someone. Health factors are themain driving factor for improving productivity in daily activities. Therefore, healthservices should be paid serious attention to the relevant parties, both government andprivate. Many health field work had been done, so much the health sector jobs thatcan not be done, such as the completeness of providing accurate data about a patient'shistory.At the Meteorological and Geophysics Agency in particular the handling of healthissues that performed by the outpatient clinic could not provide missing informationquickly because the handling is still performed manually using that data to beintegrated into an important information that still need to find some relevantdocuments for presentation to a data information.As for the proposed solution is the use of design applications that can provide rapidinformation on patient data in accordance with a medical history from the beginningthe examination, actions, decisions made by the physicians.